Bioconversão de isoflavonas glicosídicas em isoflavonas agliconas do melaço de soja - Mantovani, Daniel (2010)
Among several functional foods available nowadays, isoflavones are important due to beneficial biological effects to human health (estrogenic, antiestrogenic, antioxidant, and antifungal activity among others) particularly because of phytoestrogens, which are the most common isoflavone types and are predominantly found in legumes. They are especially abundant in soybean, its farinaceous products, and subproducts such as soy molasses. In nature isoflavones are predominantly found as glycosides (daidzin, genistin and glycitein) which are not assimilated by our organism due to the presence of sugar in their composition. For the assimilation of isoflavones to occur in the body, it is necessary that they are in their aglycone form (without the presence of sugar molecule). The aim of this work was the bioconversion of glycoside compounds into aglycones using soy molasses as an isoflavone source. The β-glucosidase enzyme used in bioconversion was produced from different filamentous microorganisms of the genre Aspergillus (niger ATCC 16404, oryzae ATCC 1003, niger isolated from soil at the 'Laboratório Ambiental' of 'Itaipu Binacional', niger isolated from indoor atmosphere at the 'Laboratório Ambiental' of 'Itaipu Binacional') using the process of solid state fermentation (SSF), and wheat bran and defatted soy flour as substrates. The crude extract containing the enzyme β-glucosidase was used directly to the bioconversion process without prior purification treatment. The highest enzyme specific activity value, 7.6 U/mg, was obtained using Aspergillus oryzae ATCC 1003 and wheat bran as substrate. The value of 5.9 U/mg enzyme activity was obtained using the Aspergillus niger indoor air employing the substrate with defatted soy flour. The reaction of hydrolysis using 16404 Aspergillus niger, Aspergillus oryzae ATCC 1003, Aspergillus niger and Aspergillus niger soil indoor air for the production of crude enzyme with β-glucosidase at 40 °C for 30 minutes provided 100% bioconversion of all glycoside compounds into aglycones. All enzymes produced in this study using the genre Aspergillus converted glycoside isoflavone compunds (daidzin and genistin) into aglycone isoflavone compounds (daidzein and genistein). Glycoside and aglycone compounds were quantified by high performance liquid chromatography (HPLC). The proposed methodology was efficient for bioconversion of aglycones into glycosides from industrial waste of soy molasses.